Peran Pemuda Dalam Pengembangan Usaha Kopi Di Kawasan Wisata Simarjarunjung - Shofwan Al Faroqy Hasibuan; R. Hamdani Harahap; Agus Purwoko (PERSPEKTIF, 2021)
This study is to analyze the role of youth in developing their knowledge of the coffee business to attract tourists to visit the Siamrjarunjung Tourism Area and its surroundings and introduce Simalungun coffee to a wider area so that it is generally known. This study uses a qualitative method. The results of this study, the development of coffee businesses in the Simarjarunjung Tourism Area and its surroundings have followed the current trends in big cities. Coffee entrepreneurs have processed coffee beans from cherries, green beans, roast beans, and have even consumed coffee. Local youth have developed their knowledge on how to manage coffee since 2016. The impact is very visible from the increased income of coffee farmers who previously sold cherries, now they can sell in the form of green beans, roast beans, and even coffee drinks clearly increase income for farmers and coffee entrepreneurs. shop. The development of the coffee shop business has also increased with the development of knowledge of coffee shop business entrepreneurs about contemporary coffee brewing techniques favored by millennials. The role of youth in increasing the selling value of coffee can be seen from the increase in the capacity of youth in understanding coffee management and even making places to enjoy coffee in the Simarjarunjung and Surrounding Tourist Areas, namely coffee shops. There are 6 (six) coffee shops in the Simarjarunjung Tourism Area and its surroundings, each of which is managed by local youths by selling various kinds of coffee products such as green beans, roast beans, and coffee drinks.